Brothers in arms one legendary tank regiment's bloody war from D-day to VE-day - Holland, James 1970- (Atlantic Monthly Press, 2021)
"In the annals of World War II, certain groups of soldiers stand out, and among the most notable were the Sherwood Rangers. Originally a cavalry unit in the last days of horses in combat, whose officers were landed gentry leading men who largely worked for them, they were switched to the "mechanized cavalry" of tanks in 1942. Winning acclaim in the North African campaign, the Sherwood Rangers then spearheaded one of the D-Day landings in Normandy on June 6, 1944, led the way across France, were the first British troops to cross into Germany, and contributed mightily to Germany's surrender in May 1945. Inspired by Stephen Ambrose's Band of Brothers, acclaimed WWII historian James Holland memorably profiles an extraordinary group of citizen soldiers constantly in harm's way. Their casualties were horrific, but nonetheless their ranks immediately refilled. Informed by never-before-seen documents, letters, photographs, and other artifacts from Sherwood Rangers' families-an ongoing fraternity-and by his own deep knowledge of the war and of tank warfare, Holland offers a uniquely intimate portrait of the conflict at ground level. He introduces heretofore unknowns such as Commanding Officer Stanley Christopherson, squadron commander John Semken, Sergeant George Dring, the remarkable regimental chaplain Leslie Skinner, and other memorable characters who helped the regiment become the single unit with the most battle honors of any ever in the British army. Following the Sherwood Rangers' brutal journey over the dramatic eleven months between D-Day and VE-Day, weaving their exploits into the larger narrative and strategy of the war, Holland argues that the U.S.-built Sherman tank in which they fought was one of the finest in action, and he presents a vivid and original perspective on the endgame of WWII in Europe"
Keywords: Zweiter Weltkrieg; Panzertruppe; Großbritannien; Great Britain / Army / Nottinghamshire Sherwood Rangers Yeomanry; World War, 1939-1945 / Campaigns / France / Normandy; World War, 1939-1945 / Campaigns / Europe; World War, 1939-1945 / Regimental histories / Great Britain; Military campaigns; Regimental histories; Europe; France / Normandy; Great Britain; 1939-1945